ANALISIS PUTUSAN TINGKAT KASASI TERHADAP PUTUSAN PENGADILAN YANG MEMBEBASKAN PELAKU TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH PENYELENGGARA NEGARA (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR : 236 K/PID.SUS/2014). - Ricky T. A Pasaribu; Muhammad Hamdan; Edi Yunara; Suhaidi Suhaidi (USU LAW JOURNAL, 2018)
ABSTRACT Debate about corruption will never end. This phenomenon is very interesting to be analyzed, let alone,in this current condition there is an indication which reflects people’s distrust in the government. The demand for clean governmentis increasing, followed by the previous economic crisis. The research problems were how about the type of corruption criminal actcommitted by government officials in the abuse of authority, how about judge’s considerationin the Medan District Court’s Ruling No. 51/Pid.Sus.K/2013/PN.Mdn, and how about the analysis on Judge’s Decision in the Higher Court on acquittal in corruption criminal act in the abuse of authority committed by Government Officials (A Case Study on the Supreme Court’s No. 236K/Pid.Sus/2014). The research used juridical normative and descriptive analytic method by using primary, secondary, and tertiary legal materials with qualitative analysis. The result of the research was related to three types of corruption offense committed by government officials such as bribery, embezzlement, fraud, extortion, and gratification. The judge’s consideration in the Medan District Court’s Ruling in the case No. 51/Pid.Sus.K/2013/PN.Mdn on acquittal for the defendant in that case, there were some errors in the decision of the Panel of Judges. They only heard the witnesses’ and the defendant’s testimonies without considering any legal provisions which regulate that case. It is recommended that the principle of good governance be implemented in all government levels and lines and all actions should be applied.   Keywords : Cassation Appeal, Corruption Criminal Act, Government Officials